Strategies for Structural Adjustment : The Experience of Southeast Asia, papers presented at a seminar held in Kuala Lumpur, Malaysia, June 28-July 1, 1989 - Abdul Aziz, Ungku (International Monetary Fund, 1990)
This collection of papers delivered at a seminar, moderated by Ungku A. Aziz, in Kuala Lumpur addresses issues of economic and structural adjustment and trade and exchange rate policies in Southeast Asia.